EDUKASI DAN INOVASI PRODUK ALBUMIN IKAN GABUS SEBAGAI NUTRISI TAMBAHAN BAGI PENDERITA LUKA DAN PASCAOPERASI - Rasmi Zakiah Oktarlina; Citra Yuliyanda Pardilawati; Sutarto Sutarto; Dinda Amelia; Rahmadani Putri Riyanto; Syaiful Bahri (Jurnal Abdi Insani, 2025)
Snakehead fish (Channa striata) is a natural source of albumin that plays a vital role in wound healing and post-operative recovery. Despite its high nutritional potential, its utilization in Hanura Village, Teluk Pandan District, Pesawaran Regency, Lampung, Indonesia, remains limited. The main challenges include its strong fishy odor and the lack of product innovation. This condition highlights the need for developing more innovative and acceptable snakehead fish-based products. To address this issue, the community service program aimed to enhance the knowledge and skills of local partners in producing snakehead fish albumin capsules through training in manufacturing, packaging, and marketing. The program employed a modified extractor and a freeze-drying method to obtain high-quality albumin extract. It also included education on efficient and simple extraction procedures and training on capsule production processes that can be easily implemented by the community. The program successfully designed and developed a modified extractor unit for albumin extraction. The extraction process produced 500 mL of liquid albumin with a yield of 27.37%, which was subsequently freeze-dried into 35.70 g of yellow albumin powder with a distinctive odor. The Biuret test yielded positive results, indicated by a color change to purple, while heating at 90 ºC caused coagulation, confirming the presence of albumin. The training involved 20 participants and resulted in a significant improvement in understanding, with average scores increasing by 71.7%, from 32.8 to 80.5. Overall, the program successfully improved participants’ knowledge and skills in producing snakehead fish albumin capsules and promoted the sustainable utilization of local resources in Hanura Village.